Yeast Species and Bioactive-Compounds of Traditional Rice Wine Originated from Lombok Island, Indonesia - I Nyoman Sumerta; Yeni Yuliani; Maya Komalasari; Ismu Purnaningsih; Atit Kanti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2022)
In fermented beverages, yeasts have been exploited for many years and are well-known as alcohol producers. In Indonesian traditional beverages, however, information about microbiology and potential bioactive-compounds of rice wine produced by the local people, especially in Lombok, are limited. The present study described the compounds of traditional rice wine including yeast species and its produced compounds that have biological activity. The yeast in rice wine was isolated using three growth agar media by serial dilution, selected the yeast colonies for molecular identification, and performed gas chromatography tandem with mass spectrometry for profiling the chemical compounds of the rice wine. The result indicated that the rice wine sold without distillation still contained Saccharomyces cerevisiae as the main alcohol producer. Meanwhile, at least six bioactive-compounds such as l-(+)-Ascorbic acid 2,6-dihexadecanoate, performic acid, octadecanoic acid, sulfurous acid, tetratriacontane, and eicosane were detected and reportedly related to antimicrobial, antiviral, anticancer, and other pharmacological activities. These findings could be the first step of studies on exploring Indonesian’s local rice wine as alcohol and bioactive-compound sources for health benefits.